Continuous ambulatory peritoneal dialysis and renal transplantation: a five year experience. Issue 6501 (12th October 1985) - Donnelly, P K; Lennard, T W; Proud, G; Taylor, R M; Henderson, R; Fletcher, K; Elliott, W; Ward, M K; Wilkinson, R
Abstract : Continuous ambulatory peritoneal dialysis is a new and increasingly popular method of routine dialysis, but its effect on renal transplantation is uncertain. A non-randomised comparison was made of the outcome of grafting in patients who had been treated before transplantation with continuous ambulatory peritoneal dialysis with that in patients treated with haemodialysis. During the five years, 1979-84, after continuous ambulatory peritoneal dialysis was introduced to Newcastle upon Tyne 220 patients have received transplants after either continuous ambulatory peritoneal dialysis (61 patients) or haemodialysis (159 patients). During follow up no significant differences occurred in survival of patients or grafts between the two treatment groups. One year after transplantation the percentages of survivors who had received continuous ambulatory peritoneal dialysis and haemodialysis were 88% and 91% respectively, and overall graft survival was 66% and 72%, respectively. A multiple regression model was used to allow for differences among patients--for example, duration of dialysis and number of preoperative transfusions--on the survival of grafts. When only first cadaver grafts were considered (in 152 patients) graft survival (non-immunological failures excluded) was not significantly different between the patients treated with continuous ambulatory peritoneal dialysis and haemodialysis. Continuous ambulatory peritoneal dialysis is not a risk factor in renal transplantation, and its continued use in treatment of potential renal graft recipients is recommended.